AB0087 Sonic hedgehog promotes fibroblast-like synoviocytes proliferation via modulating the mapk/erk signaling pathway in rheumatoid arthritis. (15th June 2017) - Liu, F; Zhu, S-L; Pan, Y-F; Huang, J-L
Abstract : Background: The Sonic hedgehog (Shh) signaling has been reported to be activated in synovium of RA patients and RA-FLS in vitro [1]. Further, Shh signaling plays an important role in RA-FLS proliferation [2]. As for the extracellular signal-regulated kinase (ERK), is a member of mitogen-activated protein kinase (MAPK) [3], which has been reported to be involved in proliferation of RA-FLS [4]. However, the role of MAPK/ERK signaling pathway in the proliferation of RA-FLS modulating by Shh is unclear. Objectives: To study the effect of MAPK/ERK signaling pathway on cell proliferation modulated by Sonic hedgehog (Shh) signaling in fibroblast-like synoviocytes isolated from patients with active rheumatoid arthritis (RA-FLS). Methods: The RA-FLS were primarily cultured by the explant culture, and then were treated with Shh agonist Purmorphamine, inhibitor Cyclopamine or MAPK/ERK signaling pathway inhibitor U0126, respectively. Western blots was used to examine the phosphorylation level of ERK 1/2 (p-ERK1/2), which was the critical protein of MAPK/ERK signaling. The cell proliferation activity was detected using cell proliferation and cytotoxicity kit-8 (CCK8), and the cell proliferation rate was detected using a flow cytometry. Results: Compared with the control group, Purmorphamine transiently increased p-ERK1/2 protein at the concentration of 1 μM, and the peak activations of p-ERK1/2 took place at 15min ( P <0.01). Cyclopamine and U0126 decreased the expression of p-ERK1/2 protein ( P <0.01). After the RA-FLS treated with Purmorphmine (1μM) for 48 hours, the cell proliferation activity was 114±4% and the percentage of S phase cells was 8.39±0.60%, significantly higher than those of the control group 100±0% ( P <0.01) and 3.29±0.69% ( P <0.01). After treated with Cyclopamine (10μM) for 48 hours, the cell proliferation activity of RA-FLS was 89±1% ( P <0.05) and the percentage of S phase cells was 1.53±0.22% ( P <0.05). When co-treated with purmorphamine (1μM) and U0126 (10μM), the cells proliferative activity was 892% ( P <0.05) and the percentage of S phase cells was 1.07±0.25% ( P <0.05). Conclusions: Shh might promote proliferaton of RA-FLS via modulating MAPK/ERK signaling, subsequently contributing to hyperlasia of synovium and ultimately leading to RA disease. References: Wang M, et al. Sonic hedgehog signaling drives proliferation of synoviocytes in rheumatoid arthritis: a possible novel therapeutic target[J]. J Immunol Res, 2014, 2014: 401903. Zhu SL, et al. Inhibition of smoothened decreases proliferation of synoviocytes in rheumatoid arthritis[J]. Cell Mol Immunol, 2015. DOI: 10.1038/cmi.2015.67. Elia D, et al. Sonic hedgehog promotes proliferation and differentiation of adult muscle cells: Involvement of MAPK/ERK and PI3K/Akt pathways[J]. Biochim Biophys Acta, 2007. 1773(9): 1438–46. Morel J, Audo R, Hahne M, Cet al. umor necrosis factor related apoptosis inducing ligand (TRAIL) induces rheumatoid arthritis synovial fibroblast proliferation through mitogen activated protein kinases and phosphatidylinositol3-kinase/Akt[J]. J Biol Chem 2005. 280(16):15709–15718. Acknowledgements: This study was supported by the National Natural Science Foundation of China (No.81571584). I thank Jianlin Huang for protocols. Disclosure of Interest: None declared